KEPASTIAN HUKUM MENGENAI JAKSA PENUNTUT UMUM DALAM MENGAJUKAN PENINJAUAN KEMBALI - Louis william (Fakultas Hukum Universitas Tarumanagara, 2021)
Review Of Court Decision or Judicial Review is regulated in law No 8 of 1981 concerning The Criminal Procedure Code/ Kitab Undang Hukum Acara Pidana (KUHAP). Article 263 paragraphs (1) (2) and (3) contain the matter of reconsideration, who is entitled to do the terms of review, however this has not been achieved optimally. Plenty of cases regarding prosecutors applying for reconsideration; which then creates no legal certainty. Nonetheless, in respect of who has the right itself, it is only the defendant or their heirs that are listed. Yet, there is no clear prohibition which expresses that the prosecutor cannot apply for reconsideration or judicial review. Whereas in making laws, there must be legality principles, that is Lex Scripta must be formally written and of certainty, Lex Stricta must be directed strictly, and then Lex Certa must be clearly stated and unambiguous. Since there is still grey area in the regulation related, therefore this journal aims to discuss about review of court decision the right of public prosecutor in conducting review of court of decision